Assessment of the extractability of protein-carbohydrate concentrate from soybean meal under acidic and alkaline conditions. (April 2019) - Gerliani, Natela; Hammami, Riadh; Aïder, Mohammed
Abstract: A soluble dry matter composed of proteins, carbohydrates, and minerals was obtained from soybean meal following both alkaline and acid extraction. The alkaline extraction was conducted at pH 8, 9, 10 whereas the acid extraction was carried out at pH 2 and 3. In both extraction modes, different NaCl concentrations were added to the medium (0.01, 0.025 and 0.05 M). The obtained results showed that both methods were effective in terms of extraction of soluble dry matter with significant qualitative and quantitative differences. The alkaline extraction was significantly more effective in terms of the total extracted dry matter and protein content in the extracted material with mean values of 39.97 ± 0.23% and 43.35% ± 2.90, respectively. The acid and alkaline extracts were characterized by high content (mg/100 g) of specific minerals such as potassium (334.93 ± 41.93), calcium (24.73 ± 10.32) and magnesium (35.34 ± 10.86). SDS-PAGE data confirmed the effectiveness of the alkaline mode in terms of quantitative protein content by the more evident bands. The highest turbidity was obtained at pH 4–5 for all the extracts whereas zeta potential indicated pI at pH 4–5 for alkaline extracts and at pH 7–8 for the acidic extracts. Carbohydrate profile showed a pH-dependent of the extracted sugars with a potential of using the extract as prebiotic. Overall, this study highlights the effectiveness and rational use of combined acid-alkaline extractions to enhance the soybean meal valorization for food applications and to reduce waste generated by the soybean oil industry. Highlights: Soybean meal was successfully valorized for the production of high value-added proteins and carbohydrates. Soybean meal was used for innovative combined acid-alkaline extraction. High added-value protein-carbohydrate concentrate was produced from soybean meal. Dual acid-alkaline extraction is effective for soybean oil industry waste reduction.